The Impact of Value-Based Leadership on the Commitment of Business Actors and the Performance of MSMEs in Purwakarta Regency - Duki Adam; Sudarto Sudarto (Citakonsultindo, 2024)
The aim of this research is to analyze the impact of values-based leadership on the commitment of business actors and the performance of MSMEs in Purwakarta Regency. This research aims to identify the extent to which ethical and moral values ​​integrated into leadership styles can increase dedication, loyalty and motivation of business actors. The population in this study was 6324 MSMEs, using the Slovin formula and an error or inaccuracy of 5%. The number of samples used in this research was 221 MSMEs in Purwakarta Regency, West Java. SmartPLS is used in this research as a research analysis tool. The results of this research are that value-based leadership has no influence on the performance of MSMEs, values-based leadership has an influence on the commitment of business actors and the commitment of business actors has an influence on the performance of MSMEs.